1976
DOI: 10.1530/jrf.0.0460017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by FSH and dibutyryl cyclic AMP of the formation of androgen-binding protein in Sertoli cell-enriched cultures

Abstract: Sertoli cell-enriched preparations from testes of 20-day-old rats were cultured in a defined medium in the presence and absence of FSH or dibutyryl cyclic AMP (dcAMP). Androgen-binding activity was assayed in the culture medium, and related to testicular androgen-binding protein (ABP). The production and secretion of ABP by the Sertoli cell-enriched preparation was increased after FSH or dcAMP treatment of the primary culture. It is concluded that ABP is produced by Sertoli cells. The possibility of involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(51 citation statements)
references
References 17 publications
2
48
0
1
Order By: Relevance
“…The actions of FSH on Sertoli cells from prepubertal animals is demonstrated biochemically by increased levels of cAMP, increased protein synthesis and increased estradiol production. 25 However, responses of Sertoli cells from adult mammals to FSH are more difficult to demonstrate and may vary from species to species. In many cases the biochemical activities of FSH in the prepubertal animal appears to be assumed by testosterone in the adult.…”
Section: Endocrine Regulation Of Spermatogenesis Via Sertoli Cellsmentioning
confidence: 99%
“…The actions of FSH on Sertoli cells from prepubertal animals is demonstrated biochemically by increased levels of cAMP, increased protein synthesis and increased estradiol production. 25 However, responses of Sertoli cells from adult mammals to FSH are more difficult to demonstrate and may vary from species to species. In many cases the biochemical activities of FSH in the prepubertal animal appears to be assumed by testosterone in the adult.…”
Section: Endocrine Regulation Of Spermatogenesis Via Sertoli Cellsmentioning
confidence: 99%
“…Similarly, in the mouse testis the accumulation of labeled PRL was detected on Leydig cells (VanhaPerttula et al, 1973). Of course, FSH binding sites were located on Sertoli cells in the seminiferous tubules (Fritz et al ., 1975;Setchell et al, 1976;Shimizu et al, 1987). It has been reported that unknown factor(s) secreted from Sertoli cells following FSH treatment augmented the responsiveness of Leydig cells to LH and increased the LH binding to cultured porcine testicular cells (Benahmed et al, 1985 a, b) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the SCs also control the ionic composition of the seminiferous epithelium [21] and the tubular fluid pH [22,23]. Fully differentiated SCs are often described as "nurse cells" and secrete several factors essential for spermatogenesis, including transferrin [24], glycoproteins [25], sulpho-proteins [26], myo-inositol [27], plasminogen activator [28] and androgen-binding protein [29].…”
Section: General Aspects Of Sertoli-germ Cell Associationmentioning
confidence: 99%